On the sunk-cost effect in economic decision-making: A meta-analytic review - Stefan Roth; Thomas Robbert; Lennart Straus (Business Research, 2015)
Although the effect of monetary sunk costs on decision-making is widely discussed, research is still fragmented, and results are sometimes controversial. One reason for this incomplete picture is the missing differentiation between the effect of sunk costs on utilization and progress decisions and its respective moderators. This article presents the results of a meta-analytic review of 98 effect sizes of the sunk-cost effect, with special emphasis on the decision-specific influence of moderators. The results show clear evidence that the sunk-cost effect emerges, though its effect size and the influence of the moderators are contingent on the respective decision type. In particular, we find support for the idea that the sunkcost effect is attenuated by time in utilization decisions. The results also reveal that older adults are less likely to fall prey to the sunk-cost effect than younger adults.
Keywords: D11; D80; 650; Sunk-cost effect; Meta-analytic review; Utilization decision; Progress decision; Escalation of commitment